Photometer (Calitoo) measurements in NetCDF format gathered during MARIA S. MERIAN cruise MSM114/2 (ARC) - Stammes, Piet; Tuinder, Olaf; Köhler, Laura (In: Köhler, Laura; Baranowski, Dariusz B; Brennek, Michał; Ciuryło, Michał; Hayo, Lennéa; Jansen, Friedhelm; Kepski, Daniel; Kinne, Stefan; Latos, Beata; Lobo, Bertrand; Marke, Tobias; Nischik, Timo; Paul, Daria; Pietruczuk, Aleksander; Stammes, Piet; Szkop, Artur; Tuinder, Olaf; Windmiller, Julia (2024): Standardized data sets of the atmospheric and oceanographic observations gathered during MARIA S. MERIAN cruise MSM114/2 (ARC) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.966616, 2024)
The ship campaign MSM114/2 (ARC) with the German research vessel Maria S. Merian took place from 22 January to 23 February, 2023. The campaign started in Mindelo, Cape Verde, and ended in Punta Arenas, Chile. During the campaign, the Intertropical Convergence Zone (ITCZ) was completely crossed three times at an almost constant longitude of 23˚W yielding three profiles of the ITCZ. Afterwards, a storm was passed in the Roaring Forties, in the South Atlantic. Here, we present data from the Calitoo as part of a series of standardised data sets of the atmospheric and oceanographic observations gathered during the ARC campaign. The Calitoo data set contains the aerosol optical thickness at 465, 540, and 619 nm and the derived Angstrom parameter.
Keywords: Atlantic; Atmosphere; ITCZ; Maria S. Merian; ship; tropical Atlantic